223. Difference in Carbapenem Use by ASP Intervention in Japanese Healthcare Facilities. (31st December 2020) - Endo, Mio; Tsuzuki, Shinya; Asai, Yusuke; Tajima, Taichi; Matsunaga, Nobuaki; Hayakawa, Kayoko; Ohmagari, Norio
Abstract: Background: Antimicrobial stewardship program (ASP) interventions have been reported to reduce unnecessary antimicrobial use (AMU). In this study, we investigated the difference in the use of carbapenems by ASP intervention in Japanese healthcare facilities. Methods: Data on two components of AMU and ASP registered in Japan Surveillance for Infection Prevention and Healthcare Epidemiology (J-SIPHE) from January to December 2019, were used. Facilities with an infection control team in addition to an antimicrobial stewardship team responsible for the proper use of antimicrobial agents were included in the study. AMU data (such as DOT [Days of Therapy / 100 patient days]) are entered semi-automatically from medical fee statement (receipt) file at each facility. ASP intervention is divided into four categories 1) pre-authorization, 2) prospective audit and feedback (PAF), 3) PAF and required notification (RN), 4) RN. The Kruskal-Wallis test is performed to see overall difference and the Dunn test with the Bonferroni correction is done for each pair of categories. Results: A total of 114 hospitals were included in the analysis. The median number of beds at participating facilities were 430 [IQR: 281–602], the median average hospital stay was 13.0 days [IQR: 11.4–15.2] and total number of inpatients per month was 10087 [6247–14536]. PAF and RN were the most common ASP interventions for carbapenems (62.5%), followed by RN (33.6%). The median DOT [IQR] of participating facilities were 2.1 [1.2–3.1] and 1) 0.7 [0.2–1.1], 2) 2.7 [2.1–3.4], 3) 2.1 [1.4–3.1] and 4) 2.0 [1.2–3.5] by ASP categories. There are significant differences between 1) and 2), 1) and 3), and 1) and 4) (p=0.014, p< 0.01 and p< 0.01, respectively) while the differences between 2) and 3), 2) and 4), and 3) and 4) are not significant (p=1.00). Table 1. Summary statistics of healthcare facilities by ASP Interventions Figure 1. DOT by ASP Interventions Conclusion: Only 3.5% of ASP interventions belong to 1) pre-authorization category and this might be due to the complexity of registration process. This category was found to have the lowest DOT among all ASP interventions in Japanese healthcare facilities. The variances of DOT were especially large in categories 3) and 4), and more detailed analyses would be necessary to evaluate their efficacies accurately. Disclosures: All Authors : No reported disclosures